Pandemic influenza preparedness (PIP) framework: Progress challenges in improving influenza preparedness response capacities in the Eastern Mediterranean Region, 2014-2017 - Abdinasir Abubakar; Amgad Elkholy; Amal Barakat; Bhagawan Shrestha; Mohamed Elhakim; Mamunur Rahman Malik; Isabel Bergeri; Gina Samaan (Elsevier, 2020)
Influenza viruses with pandemic potential have been detected in humans in the Eastern Mediterranean Region. The Pandemic Influenza Preparedness (PIP) Framework aims to improve the sharing of influenza viruses with pandemic potential and increase access of developing countries to vaccines and other life-saving products during a pandemic. Under the Framework, countries have been supported to enhance their capacities to detect, prepare for and respond to pandemic influenza. In the Eastern Mediterranean Region, seven countries are priority countries for Laboratory and Surveillance (L&S) support: Afghanistan, Djibouti, Egypt, Jordan, Lebanon, Morocco and Yemen. During 2014-2017, US$ 2.7 million was invested in regional capacity-building and US$ 4.6 million directly in the priority countries. Countries were supported to strengthen influenza diagnostic capacities to improve detection, enhance influenza surveillance systems including sentinel surveillance for severe acute respiratory infection and influenza-like illness, and increase global sharing of surveillance data and influenza viruses. This paper highlights the progress made in improving influenza preparedness and response capacities in the Region from 2014 to 2017, and the challenges faced. By 2017, 18 of the 22 countries of the Region had laboratory-testing capacity, 19 had functioning sentinel influenza surveillance systems and 22 had trained national rapid response teams. The number of countries correctly identifying all influenza viruses in the WHO external quality assurance panel increased from 9 countries scoring 100% in 2014 to 15 countries in 2017, and the number sharing influenza viruses with WHO collaborating centres increased by 75% (from eight to 14 countries); more than half now share influenza data with regional or global surveillance platforms. Seven countries have estimated influenza disease burden and seven have introduced influenza vaccination for high-risk groups. Challenges included: protracted complex emergencies faced by nine countries which hindered implementation of influenza surveillance in areas with the most needs, high staff turnover, achieving timely virus sharing and limited utilization of influenza data where they are available to inform vaccine policies or establish threshold values to measure the start and severity of influenza seasons. Keywords: Influenza, Pandemic, PIP framework, Surveillance, Eastern Mediterranean Region